In the flo : unlock your hormonal advantage and revolutionize your life - Vitti, Alisa (HarperOne, an imprint of HarperCollins Publishers, 2021)
A biohacking program for women, teaching them how to use their natural 28-day cycle to optimize their time, diet, fitness, work, and relationships. Presents a 4-week solution to manage energy and time according to female biochemistry. By working with each phase, you'll support your hormones, unlock peak creativity and performance, and avoid burnout. You'll know exactly when to eat certain foods, clear your social calendar, or ask for a raise--and you'll have the tools to do so. Includes meal plans and recipes for each phase; carts for phase-specific exercises, work tasks, and relationship activities; a daily planner that helps you align with your strengths in each phase; and a biohacking toolkit for navigating period problems and hormonal birth control.